On b-bistochastic quadratic stochastic operators and their properties - Ahmad Fadillah bin Embong (Kuliyyah of Science, International Islamic University Malaysia, 2016)
In the present thesis, we considered a majorization in term of b-order. Using such majorization, we defined bistochastic QSOs with respect to b-order, namely b-bistochastic QSOs in which it defines a new class of QSOs. Further, we provided some crucial properties of b-bistochastic QSOs in a general setting, and fully described b-bistochastic QSOs on one and two dimensional simplices. In addition, we showed that for every b-bistochastic QSOs, their trajectories were convergent. Besides, it was found that (0,0,…,1) was the fixed point of any b-bistochastic QSOs. Next, we managed to fully study the dynamics of b-bistochatic QSOs on one dimensional simplex, whereas on two dimensional simplex, we limited the study on boundaries only. Generally, it was established that the set of all b-bistochastic QSOs formed a convex set, hence we were interested to describe its extreme points. The results were presented as the list of extreme points on low dimensional simplices. Moreover, we introduced quasi-extremity of b-bistochastic QSO and investiged it on two dimensional simplex. Finally, we associated Markov measures with b-bistochastic QSOs. On some classes of b-bistochastic QSOs, the defined measures were proven to satisfy the mixing property. Moreover, we studied the absolute continuity of Markov measures associated with a class of b-bistochastic QSOs.